Life Style Among Women With Endometriosis (Journal of Pharmaceutical Negative Results, 2023)
Background: Endometriosis is benign gynecological disorders that affect women during their reproductive age and negatively effects on women's lives. Aim of the study: Was to evaluate life style among women with endometriosis. Study Design: Descriptive design was used to carry out the study. Setting: The study was carried out at gynecological outpatient clinic of Zagazig university hospitals, Sharkia governorate, Egypt as it covers a wide range of population with different characteristics with high flow rate. Subjects: A purposive sample of 132 women were included in the study who meet the criteria. Tools of data collection: Two tools were used: a structured interview questionnaire and life style assessment questionnaire. Results: The presented study found that more than half of the studied women their age was >25 years with mean ±SD 32.45±5.24, the most consumed diet by nearly half of the studied women was red meat and beef, nearly half of them were under-weight and performed low level of physical activities and there was no significant relation between total life style and personal data p-value > 0.05. Conclusion: Majority of the studied women with endometriosis had unhealthy life style and lower percentage of them had healthy life style. Recommendations: Awareness raising programs about endometriosis should be encouraged, mass media campaigns have an essential role to increase awareness toward disease and reproductive health in general.